1993
DOI: 10.2514/3.11718
|View full text |Cite
|
Sign up to set email alerts
|

Lifting line theory for supersonic flow applications

Abstract: The paper is devoted to the study of a supersonic lifting line theory intended to provide both a means of aerodynamic calculation and a benchmark for the validation of the control point position for the related constant pressure panel methods. The model is based on the small perturbations assumption. A constant distribution of bound vortices is assumed along the chord whereas the spanwise load distribution is calculated by means of trigonometrical series, formally similar to the subsonic methods. The calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The reason for the different behavior of the quasi-analytical method is that the design variables also affect the aerodynamic loads required by the EMWET method. From Figs 5 and 6 it can be deduced that the Torenbeek (1) and Howe method are insensitive to the tip thickness to chord ratio. For the turbojet aircraft, Fig.…”
Section: Methods Turboprop Aircraft Error [%] Turbojet Aircraft Error [%]mentioning
confidence: 95%
See 4 more Smart Citations
“…The reason for the different behavior of the quasi-analytical method is that the design variables also affect the aerodynamic loads required by the EMWET method. From Figs 5 and 6 it can be deduced that the Torenbeek (1) and Howe method are insensitive to the tip thickness to chord ratio. For the turbojet aircraft, Fig.…”
Section: Methods Turboprop Aircraft Error [%] Turbojet Aircraft Error [%]mentioning
confidence: 95%
“…Each method depends on the wing span, sweep angle, taper ratio and the root thickness-to-chord ratio. Except the Torenbeek (1) method, the other methods are sensitive to maximum take-off weight.Investigating the method presented by Howe (Equation (7)) closely, it can be concluded that the root chord length is canceled out by the reference wing area and the aspect ratio (as they include c r ). Hence, the Howe method is the only method that does not depend on c r .…”
Section: Methods Comparisonmentioning
confidence: 98%
See 3 more Smart Citations